PENGARUH CASH CONVERSION CYCLE DAN WORKING CAPITAL TURNOVER TERHADAP RETURN ON ASSET PADA INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mohammad Herli; Hafidhah Hafidhah (Fakultas Ekonomi dan Bisnis, 2015)
This study aimed to examine the effect of the Cash Conversion Cycle and Working Capital Turnover on Return on Assets At the Consumer Goods Industry Listed in Indonesia Stock Exchange (IDX). The method used in this research is the quantitative approach. Results showed variable cash conversion cycle (CCC) and working capital turnover (WCT) simultaneously have a significant effect on profitability (Return on Total Assets). Variabel cash conversion cycle (CCC) partially not have a significant impact on profitability (Return on Total Assets) but variable working capital turnover (WCT) partially have a significant impact on profitability (Return on Total Assets) consumer goods industry issuers listed on the Indonesia Stock Exchange during the period 2010-2014. Keyword : Cash Conversion Cycle, Working Capital Turnover, Return on Assets